2020
DOI: 10.1016/j.pnpbp.2019.109804
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunctions in schizophrenia: Beyond antipsychotics. A systematic review

Abstract: Background. Sexual dysfunctions (SD) in schizophrenia are frequent with strong impact on adherence and quality of life. Current recommendations stipulate to switch to prolactin-sparing antipsychotic in case of SD.Objectives. To synthetize in a systematic review data on the SD prevalence and the associated risk factors in schizophrenia (SZ).Methods. Medline, Google Scholar, PsychInfo, and Cochrane were explored, without any year or language restriction. Results. Overall, 89 studies and 25,490 participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 117 publications
(214 reference statements)
4
37
3
Order By: Relevance
“…The prevalence of sexual dysfunction among people with schizophrenia is higher than that among the rest of the population. Sexual dysfunction has been reported in 30–82% of patients with psychiatric disorders who use antipsychotics, due to hyperprolactinemia as well as α1 and dopamine D 2 receptor blockades ( De Boer et al, 2015 ; Dumontaud et al, 2020 ). A meta-analysis reported that olanzapine users had a higher rate of sexual dysfunction (approximately 40%) as compared with the prolactin-sparing antipsychotics quetiapine, ziprasidone, and aripiprazole (16–27%) ( Serretti and Chiesa, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of sexual dysfunction among people with schizophrenia is higher than that among the rest of the population. Sexual dysfunction has been reported in 30–82% of patients with psychiatric disorders who use antipsychotics, due to hyperprolactinemia as well as α1 and dopamine D 2 receptor blockades ( De Boer et al, 2015 ; Dumontaud et al, 2020 ). A meta-analysis reported that olanzapine users had a higher rate of sexual dysfunction (approximately 40%) as compared with the prolactin-sparing antipsychotics quetiapine, ziprasidone, and aripiprazole (16–27%) ( Serretti and Chiesa, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested a relationship between the disorders ( Ahl et al, 2004 ; Rubio-Abadal et al, 2016 ), but other studies have discovered no such relationship ( Johnsen et al, 2011 ; Kikuchi et al, 2012 ). Other factors that have been suggested to be related to sexual dysfunction in patients with schizophrenia include sex, age, disease psychopathology, effects of other medications, substance use, and medical comorbidities ( Martin et al, 2018 ; Dehelean et al, 2020 ; Dumontaud et al, 2020 ). Antipsychotic-induced sexual dysfunction can significantly distress patients and subsequently reduce drug compliance ( Souaiby et al, 2019 ); accordingly, evaluating sexual dysfunction and managing it properly are essential.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7 Sexual dysfunctions, to which clinicians pay little attention, are among the most important causes of poor quality of life and treatment noncompliance. 8 Effectively managing the side effects that occur during mental health treatment, facilitating drug compliance and achieving the best possible results are important for patients' sexual health. 9 Patients' inability to express their sexual problems, healthcare professionals' belief that individuals with mental illnesses do not have sex lives and clinicians' avoiding talking about these issues with patients further increase patients' problems.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the general population, individuals with serious mental disorders exhibit lower rates of contraceptive use and have a higher risk of engaging in risky sexual acts and being exposed to harassment and rape, unwanted pregnancies, and sexually transmitted diseases 5,6,7 . Sexual dysfunctions, to which clinicians pay little attention, are among the most important causes of poor quality of life and treatment noncompliance 8 . Effectively managing the side effects that occur during mental health treatment, facilitating drug compliance and achieving the best possible results are important for patients' sexual health 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The endocrine system is another postulated source for the chronic inflammation associated with schizophrenia. Especially implicated are certain conditions including metabolic syndrome, obesity, and diabetes as well as basic differences in disease pathophysiology between males and females (11)(12)(13). These conditions are often the result of antipsychotics that slow metabolism and contribute to weight gain and a disrupted metabolic state.…”
Section: Introductionmentioning
confidence: 99%